Trajectory Tracking Control of Two-link Robotic Manipulator Using PID and MPC Controllers (Journal of Academic Research, 2024)
This paper discusses the difference between two tracking control strategies for a two-link robotic manipulator and compares the tracking results of the two strategies, in terms of accuracy and overshoots prevention. The design and simulation of the control approaches are based on the development of a nonlinear model for the complex dynamics of the manipulator system. The system modeling is based on Euler-Lagrange equations. The first strategy is a Proportional Integral Derivative (PID) control. Its design is based on the trial and error online tuning method, which is applied directly to control the two-joints of the robotic manipulator. On the other hand, the second strategy is a novel Model Predictive Control (MPC) strategy, which its design is based on feedback linearization analysis technique that utilizes the nonlinear model of the manipulator’s complex dynamics to design a feedback linearization control strategy to work as a primary control loop.
Keywords: Model Predictive Control (MPC); Proportional Integral; • Two-link Robotic Manipulator; Feedback Linearization Control